Structural Applications of Lumber in Construction - Tayade, Saurabh; Nikam, Nikita; Kamble, Premalata; Vaidya, Rachana (Journal of Progress in Civil Engineering, 2025)
In this Review paper we will focus on the various lumber species & growth rates. We will see the percentage of moisture content required in lumbers taking the perspective of their durability and sustainability. Strengths and various treatments carried out on wood to make them better in chemical resistances are elaborated. We have reviewed the fire resistance characteristics required to make the structure fire-proof. It also includes the approach of reduce, reuse and recycle of waste lumber for various purposes. Crosslaminated timber connections and the Suitability of various species as per conditions at the site are also elaborated.